Mapas conceituais como jogos didáticos para o ensino-aprendizagem de física - Oliveira, Luiz Gustavo Damasceno (2020)
Conceptual Maps (CM) are graphical tools used for the organization and representation of knowledge. This tool can also be used as an evaluation method, helping to monitor the teachinglearning process. However, the first contact with the CMs by students and faculty demands more attention and time, especially for better training in the field of map development technique. Thus, a didactic game was developed as an educational product whose functionality can facilitate the construction of the first maps, as well as assist in the development of didactic practices in the teaching of Physics and in the evaluation of the learning of scientific concepts. The initial proposal of the educational product would be to apply the didactic game in 5 classes of first grades of high school in a state school in Rio Grande do Norte. However, due to the Sars-CoV-2 pandemic, face-to-face classes in state education were suspended throughout the year 2020. For this reason, we focus on a pilot application and on deepening the theoretical and methodological aspects of the dissertation and the educational product, as well as in the selfcritical analysis of the work. We realized that the didactic game functioned, in fact, as a tool for the construction of the first conceptual maps, promoted discussions among the participants, and resulted in a conceptual map with the expected structure. Finally, we highlight that the physical structure, design and theme of the card game developed as an educational product proved to be highly versatile, being able to be applied in different school subjects and in the approach of a wide range of curricular contents.